2016
DOI: 10.1007/s13199-016-0401-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of Prauserella sp. Am3, an actinobacterium isolated from root nodules of Alnus nepalensis in India

Abstract: A novel actinomycete strain, assigned as Am3, was isolated from the root nodules of Alnus nepalensis at Mirik hills, India. Analysis of the 16s rRNA gene sequence placed this new strain within the genus Prauserella. The genome was sequenced by Illumina sequencing and resulting 5.33-Mbp high quality draft genome sequenced with a G + C content of 70.0 % and 4828 candidate protein-encoding genes. Phylogenetically, Prauserella clusters very close to Amycolatopsis and was previously placed under the genus Amycolato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Although average nucleotide identities based on MUMmer (ANIm) supported the classification of these strains within the genus, the percentage of conserved proteins indicated that A. halophila might belong to a different genus ( Adamek et al, 2018 ). A five gene MLSA (with atpI , gyrA , ftsZ , secA and dnaK ) also indicated that A. halophila is more similar to members of the genus Prauserella than to Amycolatopsis species ( Bose et al, 2016 ). Therefore, we have applied a more comprehensive phylogenetic and taxogenomic approach to the genus ( Sangal et al, 2016 ) and analyzed 57 Amycolatopsis genome sequences belonging to 34 species, including five sequenced by us in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Although average nucleotide identities based on MUMmer (ANIm) supported the classification of these strains within the genus, the percentage of conserved proteins indicated that A. halophila might belong to a different genus ( Adamek et al, 2018 ). A five gene MLSA (with atpI , gyrA , ftsZ , secA and dnaK ) also indicated that A. halophila is more similar to members of the genus Prauserella than to Amycolatopsis species ( Bose et al, 2016 ). Therefore, we have applied a more comprehensive phylogenetic and taxogenomic approach to the genus ( Sangal et al, 2016 ) and analyzed 57 Amycolatopsis genome sequences belonging to 34 species, including five sequenced by us in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Those phyla are dominant in the intestinal microorganisms of crustaceans [1]. In day 10 sample, Oceanicaulis, Aliihoeflea, Prauserella, Chelativorans, Shewanella and Pseudoalteromonas were significantly increased, these genuses may involve in carbohydrate metabolism, amino acid metabolism, protein metabolism and amino acids metabolism [16][17][18][19][20][21]. Their changes showed that the balance between microorganisms of shrimp was destroyed as the host died and the environment changed, which may adversely affect muscle quality [1,22].…”
Section: Microbiome Analysismentioning
confidence: 99%
“…The result showed that gluconic acid increased significantly during storage, and had significantly relationship with Oceanicaulis, Aliihoeflea, Prauserella, Chelativorans and Pseudoalteromonas. Aliihoeflea and Chelativorans has been report to utilize the carbohydrates as their carbon source for growth [19,21], and Oceanicaulis and Prauserella were found be involved in carbohydrate transport and metabolism [16]. In the pre-storage, these microorganisms significantly increased, and the content of gluconic acid also increased; besides, most of organic acids and derivatives (e.g.…”
Section: Organic Acids and Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides Frankia, other bacteria have been isolated from actinorhizal nodules and sequencing them has become a convenient approach to gain knowledge on their function and physiology (Bose et al 2016;Ghodhbane-Gtari et al 2014).…”
mentioning
confidence: 99%